2021
DOI: 10.1021/acs.jpcc.0c11109
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Optical Force Generated by a Superchiral Near-Field of a Plasmonic Triangle Trimer as Origin of Giant Bias in Chiral Nucleation: A Simulation Study

Abstract: We previously reported that giant crystal enantiomeric excess (CEE) can be obtained when sodium chlorate (NaClO3) chiral crystallization from a solution is induced by the excitation of localized surface plasmon resonance (LSPR) of a Au triangle trimer nanostructure by a circularly polarized laser. However, the role of the LSPR excitation in the giant CEE remains unclear. In this work, we showed, by finite-difference time-domain analysis of plasmonic near-field, that the magnitude of a chiral optical gradient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…270 In a follow-up paper, the same group explained this result by modeling the plasmonic near-field during illumination and showing that the large enantiomeric excess previously observed arose from a difference in the frequency of attachment of chiral crystalline clusters to crystal nuclei, or in the local concentration of NaClO 3 due to chirally biased diffusion, rather than from enantioselective optical trapping. 271 A similar light polarization-dependent chiral synthesis was documented using chiral metallic particles, which exhibited a different photocatalytic activity depending on the helicity of the illuminating light. 272 These observations may be explained by considering the different emission rates of hot electrons in chiral plasmonic particles upon illumination with circularly polarized light, [273][274][275] as experimentally measured by Fang et al in split ring resonators deposited on a semiconductor.…”
Section: Chiral Catalysismentioning
confidence: 81%
“…270 In a follow-up paper, the same group explained this result by modeling the plasmonic near-field during illumination and showing that the large enantiomeric excess previously observed arose from a difference in the frequency of attachment of chiral crystalline clusters to crystal nuclei, or in the local concentration of NaClO 3 due to chirally biased diffusion, rather than from enantioselective optical trapping. 271 A similar light polarization-dependent chiral synthesis was documented using chiral metallic particles, which exhibited a different photocatalytic activity depending on the helicity of the illuminating light. 272 These observations may be explained by considering the different emission rates of hot electrons in chiral plasmonic particles upon illumination with circularly polarized light, [273][274][275] as experimentally measured by Fang et al in split ring resonators deposited on a semiconductor.…”
Section: Chiral Catalysismentioning
confidence: 81%
“…The nanoassembly was able to produce chiroplasmonic waves via chirality transfer for helicene to plasmonic bands. The helicene used were rac-9-(3-pyridylethylnyl) [7]helicene, rac-9-(4-pyridylethynyl) [7]helicene and racemic 2-(3-thienyl) [6]helicene. The complete information of a molecule in the solution was analysed with "cross" functionalization of the helicene enantiomers.…”
Section: Biosensingmentioning
confidence: 99%
“…Life on earth manifests a priority for L-amino acids and D-sugars, in spite of a thermodynamic stability equilibrium of the L-and D-enantiomers of these molecules. The bioactivities of a chiral molecule depend on its handedness; for example, one enantiomer might act as a drug while the other might be toxic [7]. Accordingly, chirality of molecules has a vital role in functionality and interaction with other molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, such a photothermal CD effect has been used to achieve selectively melting biomolecules located at the gap region of the chiral gold nanorod dimers (GNR-dimers). Besides, strong interaction of CPL with chiral plasmonic nanostructures can also generate remarkable chirality-dependent optical forces/torques. Early studies , have found that those chirality-dependent optical forces/torques can give rise to asymmetric optomechanical effects, such as polarization-dependent pushing/pulling of a chiral nanoparticle. In a previous experimental study, we have proposed and demonstrated that CPL-induced asymmetrical optomechanical perturbations can be used to enable dynamic chiral configurations of the GNR-dimers in solution phase.…”
mentioning
confidence: 99%